Unlocking the Sustainable Development Path of China’s Nonferrous Metal Industry Based on Collaborative Innovation - Jing Zhang; Yuanyuan Lu; Xiangmin Zhang (Discrete Dynamics in Nature and Society)
The sustainable development of an industry is an important topic of technological innovation. To unlock the path dependence of industrial development, it is critical to identify the evolution law of the industrial collaborative innovation network. Taking China’s nonferrous metal industry as an example, this paper establishes two collaborative innovation networks from the time and space dimensions, respectively. The networks cover both the macroenvironment and the microinnovative subjects of the industry and fully consider the collaborative relationships between these subjects. Through multilevel and multidimensional analysis, the authors drew the following conclusions: the macropolicies and technology paradigm can create a window of opportunity for the industry, which directly drives the breeding of new industries and the transformation and upgrading of traditional industries; the interaction between the macroenvironment and microinnovative subjects leads to the differentiation of the industrial innovation path; the provinces can enter the first echelon of interprovincial innovation collaboration and realize sustainable development of the industry through the unlocking path, which consists of path continuation, path expansion, path implantation, and path diversification.